Barriers to Contraceptive Use Among Urban Adolescents and Youth in Conakry, in 2019, Guinea - Dioubaté, Nafissatou; Manet, Hawa; Bangoura, Charlotte; Sidibé, Sidikiba; Kouyaté, Mariama; Kolie, Delphin; Ayadi, Alison M. El; Delamou, Alexandre (Frontiers in Global Women's Health, 2021)
Background: Despite efforts to improve access to family planning, contraceptive prevalence remains relatively low among adolescents and youth in Guinea. The objective of this study was to understand the barriers to adoption and use of modern contraceptive methods among urban adolescents and youth (15-24 years) in Conakry, Guinea. Methods: This was a qualitative study using an exploratory design. It was conducted in the capital city of Guinea, Conakry in 2019. Respondents included adolescents and youth aged 15 to 24 years, healthcare providers, and parents of adolescents and youth. In-depth individual interviews (IDIs) and focus group discussions (FGDs) were used to collect the data. 56 IDIs and 10 FGDs were conducted in the five communes of Conakry. These data were recorded and transcribed, when applicable, from the local languages into French, in an anonymous manner. The data were analysed using a mixed (inductive and deductive) thematic approach following the elements of the socio-ecological model. Results: Overall, 56 IDIs and 10 FGDs were conducted with 136 participants and included in this analysis. Respondents were adolescents (16%), youth (30%), and key informants (54%) who were healthcare providers (public and private), decision makers, parents of adolescents and youth, and neighbours. Among adolescent respondents, 75% were female, and of the youth, 61% were female. Our analysis indicates the existence of various and interrelated barriers that limit the access and use of contraceptive by adolescents and youth. These included the individual (fear of side effects, stigma, cost, and rumour-related misinformation), interpersonal or family (spouse perception and sexuality taboo), sociocultural (religious prohibitions, ethnicity), and facility-related (contraceptive availability, provider attitudes, visiting hours, and geographic proximity of services) barriers. Conclusion: In our context, the use of modern contraceptive methods by adolescents and youth is influenced by an interaction of diverse barriers including individual, interpersonal and socio-cultural factors. Strengthening contraceptive uptake interventions by involving different stakeholders including adolescents, parents, religious and community leaders and improving the quality of sexual and reproductive health services would help reducing barriers to contraceptive use among adolescents and youth.